2012
DOI: 10.5402/2012/125864
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of β-Glucan

Abstract: β-Glucans extracted from barley, which mainly contains β-(1,3-1,4)-D-glucan, are used extensively as supplements and food additives due to their wide biologic activities, including a reduction in blood lipid level. In this study, the antioxidant activity of β-glucan was examined to assess potential new benefits associated with β-glucan, because oxidative stress is considered one of the primary causal factors for various diseases and aging. β-Glucan extracted from barley was found to possess significant antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 13 publications
5
79
0
Order By: Relevance
“…Arguably, the nature of interaction between the β-glucan content and the contamination with DON and its role in resistance is source of debate. On the one hand, a higher β-glucan content might enhance the resistance against DON accumulation thus contributing to type V resistance by antioxidant activity of β-glucan (Kofuji et al 2012). Indeed, several studies demonstrated the inhibitive potential of natural antioxidant compounds on the production of mycotoxins (Boutigny et al 2010;Pani et al 2014;Zhou et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, the nature of interaction between the β-glucan content and the contamination with DON and its role in resistance is source of debate. On the one hand, a higher β-glucan content might enhance the resistance against DON accumulation thus contributing to type V resistance by antioxidant activity of β-glucan (Kofuji et al 2012). Indeed, several studies demonstrated the inhibitive potential of natural antioxidant compounds on the production of mycotoxins (Boutigny et al 2010;Pani et al 2014;Zhou et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, tracing the content in β-glucan of the grain after infection will help to understand the impact of the infection on the grain's biochemical composition and metabolism. β-glucan also possesses antioxidant activity (Kofuji et al 2012). Antioxidant compounds are a recognized factor of the plant's defence system to cope with biotic aggressors (Lattanzio et al 2006;Zhou et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…β-Glucan is a natural component of grain that possesses important antioxidant activity (Kofuji et al, 2012).Polysaccharides from plants have been demonstrated to be one of most promising groups of antioxidant compounds (Ng et al, 2004). Polygalacturonase extracted from barley exerts a noteworthy antioxidant effect as well as various biological activities (Kofuji et al, 2012).…”
Section: Biochemical Estimationmentioning
confidence: 99%
“…Polygalacturonase extracted from barley exerts a noteworthy antioxidant effect as well as various biological activities (Kofuji et al, 2012).…”
Section: Biochemical Estimationmentioning
confidence: 99%
“…β- (1,3) glycosidic bonds in the molecule 3 of oat beta-glucan allow solubility in water and indicate several biological activities. Among recently studied is the ability to scavenge reactive oxygen species (ROS) like very reactive hydroxyl radicals [5]. Moreover beta-glucans are also claimed to enhance the host immune system and increase organism defense against invading pathogens, as well as alleviate inflammation [6].…”
Section: Introductionmentioning
confidence: 99%